A FRAMEWORK TO IMPROVE PERFORMANCE MEASUREMENT IN ENGINEERING PROJECTS. Issue 4 (28th December 2017) - Zheng, Li; Baron, Claude; Esteban, Philippe; Xue, Rui; Zhang, Qiang
ABSTRACT: Performance measurement enables project managers to monitor the project progress and evaluate results. However, several issues remain, such as an unbalanced use of leading and lagging indicators. Lagging indicators are used to track how things are going. Leading indicators are used as precursors to the direction towards which things are going. The goal of this paper is to develop leading indicators to improve the measurement of projects performance. To address this issue, we consider the measurement processes and indicators in systems engineering measurement that promotes leading indicators. Our objective is to extend the performance measurement activities in the Project Management Body of Knowledge (PMBoK version 5) by adapting the good practices in systems engineering measurement resulting in the proposal of a framework. Thereby, systems engineering leading indicators can be applied to project performance measurement, thus providing project managers with a wider type of indicators and measurement techniques.